Enhancement of agro-industrial waste composting via the microbial inoculation: a brief review - Mohd Zainudin, Mohd Huzairi; Zulkarnain, Aisyah; Azmi, Ain Sahira; Muniandy, Shalini; Sakai, Kenji; Shirai, Yoshihito; Hassan, Mohd Ali (Multidisciplinary Digital Publishing Institute, 2022)
Composting is an important technology used to treat and convert organic waste into value-added products. Recently, several studies have been done to investigate the effects of microbial supplementation on the composting of agro-industrial waste. According to these studies, microbial inoculation is considered to be one of the suitable methods for enhancing the biotransformation of organic materials during the composting process. This review provides up-to-date research findings on microbial inoculation strategies and their role and functions in enhancing the composting process and the improvement of compost quality. Based on this review, the addition of microorganisms could enhance the composting process such as accelerating the organic matter degradation, mineralization and microbial enzymes activities, and the quality of the end-products such as high germination index. It is important to notice in this strategy that sludge’s microbial consortium is feasible to enhance the composting process in pilot-scale and industrial-scale productions. Besides, it also reduces the cost of compost production. The findings of this review show the various positive impact of microbial inoculation on agro-industrial waste composting which in turn might be useful as a reference for selecting a suitable inoculum based on the type of waste materials.